On Separability Properties of Nilpotent Groups - Wong, K.B.; Wong, P.C. (Malaysian Journal of Science, 2009)
In this note we will investigae the subgroup saperability and double coset saperability of extention of generated nilpotent groups. We then apply our results to give new proofs that fennite extentions of finitely generated nilpotent groups are subgroup saperable and double cosed separable.